Degradation of CT Low-Contrast Spatial Resolution Due to the Use of Iterative Reconstruction and Reduced Dose Levels - McCollough, Cynthia H; Yu, Lifeng; Kofler, James M; Leng, Shuai; Zhang, Yi; Li, Zhoubo; Carter, Rickey E (Radiology, 2015)
To determine the dose reduction that could be achieved without degrading low-contrast spatial resolution (LCR) performance for two commercial iterative reconstruction (IR) techniques, each evaluated at two strengths with many repeated scans. Two scanner models were used to image the American College of Radiology (ACR) CT accreditation phantom LCR section at volume CT dose indexes of 8, 12, and 16 mGy. Images were reconstructed by using filtered back projection (FBP) and two manufacturers' IR techniques, each at two strengths (moderate and strong). Data acquisition and reconstruction were repeated 100 times for each, yielding 1800 images. Three diagnostic medical physicists reviewed the LCR images in a blinded fashion and graded the visibility of four 6-mm rods with a six-point scale. Noninferiority and inferiority-superiority analyses were used to interpret the differences in LCR relative to FBP images acquired at 16 mGy. LCR decreased with decreasing dose for all reconstructions. Relative to FBP and full dose, 25%-50% dose reductions resulted in inferior LCR for vendors 1 and 2 for FBP and 25% dose reductions resulted in inferior and equivalent performance for vendor 1 and equivalent and superior performance for vendor 2 at moderate and strong IR settings, respectively. When dose was reduced by 50%, both IR techniques resulted in inferior LCR at both strength settings. For radiation dose reductions of 25% or more, the ability to resolve the four 6-mm rods in the ACR CT accreditation phantom can be lost.